Pemanfataan Bahan Lokal (Minyak Kelapa,Kunyit Dan Minyak Pala) Sebagai Oil Nassage Pada Ibu Postpartum - Sitti Hubaya Matjino; Supriyanti R Usman (Barongko: Jurnal Ilmu Kesehatan, 2025)
One of the efforts to maintain the mental health of postpartum mothers is to pay attention to the comfort of the mother so that postpartum mothers can undergo the postpartum period with a healthy physical and mental state. Postpartum mothers need to avoid stress that can reduce the quality of health, one therapy that can increase the comfort of postpartum mothers is through massage. Massage using essential oils is known as one of the non-pharmacological therapies that can be used as an alternative to pharmacological therapy. The use of local herbs such as coconut oil, turmeric and nutmeg oil is one form of application of local wisdom that can introduce the benefits of native Indonesian medicinal plants. One of them is a native plant from the city of Ternate. The purpose of this study was to determine the benefits of local ingredients (coconut oil, turmeric and nutmeg oil) as massage oil for postpartum mothers. The method used was an experimental laboratory using descriptive analysis. The study was conducted at the Pharmacy Laboratory of Khairun University, Ternate. The results of the Oil Preparation for massage on Postpartum mothers through Organoleptic and homogeneity tests, pH tests, spreadability, stickiness (seconds), viscosity tests (cp) and irritation tests. the results obtained from the organoleptic tests include clear yellowish color, thick texture and distinctive nutmeg aroma, pH oil test 7.06 which is in accordance with SNI standards 4.5-8, spreadability test 6.5 according to SNI standards, very good adhesive power 4.47 seconds according to SNI standards, Viscosity test (cP) 3300 according to SNI standards while the irritation test has negative results. The conclusion of the Massage oil preparation was declared successful through 2 trials and errors.